Durability and fire resistance of compressed wheat-straw (triticum aestivum) panels subjected to real-world aging environments - Loh, Thomas W.; Nguyen, Kate TQ (Industrial crops and products, 2023)
This paper presents an investigation into the durability of cereal straw-building materials after fifty years of use in the Australian climate. Unfortunately, the performance and durability of natural materials such as cereal straw have historically been negatively preconceived compared to their synthetic counterparts. Investigation on their potential application is needed to understand the sustainability of both the agricultural and building and construction industries. Using a compressed wheat straw (triticum aestivum) insulation panel, the effect of half a century of real-world service was assessed at the stem and panel scales. The investigation at the stem scale indicated no change to composition or degradation to microstructure, which correlated to full retainment of the panels' functional properties. The mean stem breaking force for the aged straw was measured to be within +15% of the pristine straw. At the panel scale, the mechanical properties and insulative performance were found to be statistically unaffected by the real-world aging. The compression strength and thermal conductivity of the aged panel were within +7% of the pristine panel, while the flexural strength was subject to a larger difference of +35% due to manufacturing methodology changes over last fifty years. The panels resistance to fire was also found to be maintained with each panel showing nearly identical through-the-thickness penetration of the thermal, char (+4%) and char oxidation (−10%) fronts after two hours of heat exposure. The panels were further revealed to generate a very stable char phase which contributed to the excellent fire resistance. •Natural materials (e.g. cereal straw) are susceptible to environmental degradation.•Concern exists over their long-term durability due to real-world aging.•Natural straw insulation panels aged for 50 years under Australian conditions.•Straw composition and microstructure remain intact.•Functional properties and fire resistance of panel remain after 50 years of service.